2015
DOI: 10.1080/10937404.2015.1051611
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Exposure to Carbon Nanotubes (CNT) and Carbon Nanofibers (CNF): Methodology and Dosimetry

Abstract: Carbon nanotubes (CNT) and nanofibers (CNF) are used increasingly in a broad array of commercial products. Given current understandings, the most significant life-cycle exposures to CNT/CNF occur from inhalation when they become airborne at different stages of their life cycle, including workplace, use, and disposal. Increasing awareness of the importance of physicochemical properties as determinants of toxicity of CNT/CNF and existing difficulties in interpreting results of mostly acute rodent inhalation stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 261 publications
(455 reference statements)
0
97
0
1
Order By: Relevance
“…Concerning the physical features, the diameter seems to be the main factor controlling the ability of fibers to reach the lower respiratory tract, while macrophage phagocytosis is more dependent on fiber length [7,74]. According to [4], an elongated particle is defined as "inhalable" for humans when its diameter is <3.5 µm, while [19] considers as inhalable the fibers with a diameter-length ratio ≥1:3, a length >5 µm, and a diameter <3 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the physical features, the diameter seems to be the main factor controlling the ability of fibers to reach the lower respiratory tract, while macrophage phagocytosis is more dependent on fiber length [7,74]. According to [4], an elongated particle is defined as "inhalable" for humans when its diameter is <3.5 µm, while [19] considers as inhalable the fibers with a diameter-length ratio ≥1:3, a length >5 µm, and a diameter <3 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised about health risks due to MWCNT exposure 5. Evidence from in vitro and animal studies has shown that MWCNTs can induce genetic lesions, oxidative stress, acute or persistent pulmonary inflammation, pulmonary fibrosis, cardiovascular effects and for the rigid types of MWCNTs mesothelioma-like effects 2 6.…”
Section: Introductionmentioning
confidence: 99%
“…Further, when incorporated into consumer’s products like cosmetics, drug powder form, and condiments, and in surgical or postoperative procedures, the general population may be at risk (Peng et al, 2011; Brown et al, 2013; Zhang et al, 2016). Because of their nanoscale features, inhalable nanomaterials are easily deposited deeper in the lung compared to larger particles (Buzea et al, 2007; Oberdörster et al, 2015). Further, the high aspect ratio of CN along with fibrous nature may impose safety concerns (Shvedova et al, 2014; Cyphert et al, 2016; Snyder-Talkington et al, 2016).…”
mentioning
confidence: 99%